Anti-allergic, anti-caries and whitening toothpaste and preparation process thereof

Through the combination of herbal extract and high specific surface area Ti/Zn-Ox material, the shortcomings of toothpaste in anti-allergic, anti-carious and whitening effects are solved, and teeth cleaning and sensitivity are achieved. The toothpaste is delicate and bright, and the operation is simple. , low cost.

CN119302881APending Publication Date: 2025-01-14YIWU AISHANG COMMODITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411452247.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing toothpastes are difficult to achieve anti-allergic, anti-carious and whitening effects at the same time, and there are problems of tooth sensitivity and poor oral cleaning.

Method used

Using herbal plant mixture extract and high specific surface area Ti/Zn-Ox material, nanopolyhedral Ti/Zn-Ox is synthesized by solvothermal method, and the porous hollow cage-shaped Ti/Zn oxidation is obtained by reducing L-alanine. To prepare anti-allergic and anti-carious whitening toothpaste.

Benefits of technology

It significantly improves the anti-allergic and anti-carious effects of toothpaste, enhances the cleaning ability of teeth, reduces teeth sensitivity, and has good antibacterial and acid-resistant properties. The toothpaste body is delicate and bright, simple to operate, and has low production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119302881A_ABST
    Figure CN119302881A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of oral care products, and particularly relates to preparation of anti-allergy and anti-caries whitening toothpaste. According to the invention, herbaceous plants are mixed, the mixed extracting solution is extracted, and components in the extracting solution can be combined with apatite in teeth, so that the toothpaste has the effects of resisting acid and preventing tooth decay. In addition, catechin in the green tea can reduce the existence of streptococcus mutans, slow down tooth decay and remove smelly breath. Lentinan contained in the lentinus edodes is beneficial for preventing bacteria in the oral cavity from producing dental plaque. In addition, the Ti / Zn-Ox prepared by using the Ti / Zn metal organic framework has a large specific surface area, and can well adsorb bad breath. When being used in the subsequent toothpaste preparation process, the antibacterial whitening effect can be achieved, and the high specific surface area is matched with the subsequent mixed dry powder to synergistically achieve the anti-allergy and anti-caries effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of oral care products, and specifically relates to an anti-sensitivity, anti-caries and whitening toothpaste, and in particular to an anti-sensitivity, anti-caries and whitening toothpaste and a preparation process thereof. Background Art

[0002] Tooth sensitivity, commonly known as "inverted teeth", is caused by the exposure of dentin and the opening of dentinal tubules. The treatment of tooth sensitivity can be roughly divided into two categories: blocking dentinal tubules and calming the pulp nerves. Most people's tooth sensitivity should be a mild symptom, which can be relieved by using anti-sensitive toothpaste for a period of time; for patients with severe tooth sensitivity symptoms, they must go to the dentistry department for examination and treatment in time. Sensitive teeth are also called dentin sensitivity. Dentin is located under the tooth enamel. When this softer tooth tissue is gradually exposed, it will cause sensitive teeth. The tiny tubules in the dentin are also called dentinal tubules. They not only contain nerve endings, but are also filled with fluid. These tiny tubules are 100 times smaller than the width of human hair. When these tiny tubules of dentin are exposed to cold or hot stimuli, they will cause pain and discomfort. When we eat or drink some hot, cold or sweet food and drinks, it may cause the flow of fluid in the dentinal tubules, which in turn causes the nerve endings to react, causing short and sharp pain in the teeth. Therefore, tooth sensitivity is the most common problem faced by people.

[0003] Today's society advocates naturalness and health, and the safety and efficacy of products have attracted much attention. The same is true for oral care products. Plant herbs have the advantages of small side effects and high safety of use, and have become the mainstream of market consumption. Green tea has always been regarded as a synonym for longevity and health. In addition to having strong antioxidant capacity, it also helps to prevent various disease risks. In addition, green tea contains a large amount of fluoride, which can be combined with apatite in teeth, and has the effect of acid resistance and tooth decay prevention. At the same time, studies have also shown that catechins in green tea can reduce Streptococcus mutans that cause tooth decay in the mouth and remove bad breath. Mutant mushrooms are popular foods for improving immunity. Studies have found that the lentinan polysaccharides contained in lentinus mushrooms help inhibit bacteria in the mouth from producing dental plaque. Most of the components of toothpaste are abrasives. The role of toothpaste is mainly as an intermediary, acting between the toothbrush and the teeth, enhancing the friction between the toothbrush and the teeth, and prompting the toothbrush to clean the teeth. In addition to whitening, anti-sensitivity and anti-caries are also of great significance to toothpaste. Therefore, the present invention develops a mixed extract of herbal plants and a Ti / Zn-O with a high specific surface area. x To enhance the anti-allergic and anti-caries effects of toothpaste, which is of great significance for improving people's lives. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a toothpaste or a medicinal composition, specifically an anti-allergic, anti-caries and whitening toothpaste or a medicinal composition and a preparation process thereof. This is achieved through the following technical solutions:

[0005] S1, prepare mixed extract: weigh 30-55g of shiitake mushrooms, 18-36g of green tea, 3-5g of mint leaves, 8-11g of isatis root and 5-7g of jasmine, mix them evenly, grind and mash them, add 220mL of deionized water, decoct for 8 times, 32min each time, combine the filtrate, and obtain mixed extract by distillation. The green tea extract in this step contains a large amount of fluorine, has a strong antioxidant capacity, can be combined with apatite in teeth, and has the effect of acid resistance and tooth decay prevention. In addition, the catechins in green tea can reduce the presence of mutans streptococci, slow down tooth decay, and remove bad breath. The shiitake polysaccharides contained in shiitake mushrooms help prevent bacteria in the mouth from producing dental plaque. In the mixed extract, shiitake mushrooms, green tea, mint leaves, isatis root and jasmine complement each other, have a certain inhibitory effect on different bacteria in the oral cavity, and can better achieve the effect of anti-sensitivity and tooth decay prevention.

[0006] S2. Take an appropriate amount of molecular sieves in a crucible, put the crucible into a muffle furnace, and heat treat at 310-350℃ for 4-5h. After cooling to room temperature, put the heat-treated molecular sieves into N, N-dimethylformamide (DMF) and methanol solution, fully absorb water, and obtain anhydrous DMF and anhydrous methanol; then weigh 0.3-0.45g of 2-aminoterephthalic acid in a 50mL polytetrafluoroethylene reactor, measure 6-8mL anhydrous DMF and 8-11mL anhydrous methanol and add them to the above reactor, then quickly add 0.2-0.4mL of tetraisopropyl titanate and 0.1-0.25g of zinc sulfate to the reactor, and stir it evenly. Put the polytetrafluoroethylene reactor into a stainless steel reactor sleeve, and then put it into an electric constant temperature blast drying oven, and heat treat it at 150-180℃ for 12-18h. After the reaction is completed, the reactor is cooled to room temperature, centrifuged to remove the supernatant, the yellow precipitate is collected, and the yellow precipitate is washed 3-5 times with anhydrous DMF and anhydrous methanol respectively, centrifuged to remove the DMF and methanol solutions, the yellow precipitate is collected, and vacuum dried at 60-80°C for 6-9h to obtain a nano-polyhedral Ti / Zn metal organic framework.

[0007] S3. Weigh 0.05-0.18 g of the Ti / Zn metal organic framework prepared in step S2 and place it in a 50 mL polytetrafluoroethylene reactor. Measure 8-11 mL of anhydrous ethanol and add it to the reactor. Then add 0.05-0.08 g of L-alanine to the reactor and stir it evenly. Place the polytetrafluoroethylene reactor in a stainless steel reactor jacket and then place it in an electric constant temperature blast drying oven and heat it at 180-190° C. for 18-22 h. After the reaction is completed, the reactor is cooled to room temperature, centrifuged to remove the supernatant, dark yellow precipitates are collected, the dark yellow precipitates are washed with anhydrous ethanol for 3-5 times, centrifuged to remove the ethanol solution, the dark yellow precipitates are collected, and vacuum dried at 60-80°C for 8-10h to obtain a porous hollow cage-like Ti / Zn oxide assembled by nanosheets; then 0.05-0.13g of the porous hollow cage-like Ti / Zn oxide assembled by the nanosheets is weighed and spread in a ceramic ark, the ceramic ark is placed in the middle part of the quartz tube of a tube furnace, and the tube furnace is set to heat up to 580-620°C at a heating rate of 5°C / min in an air atmosphere, and the temperature is kept for 30-42min, and after natural cooling, a porous hollow cage-like Ti / Zn-O composed of nanoparticles is obtained. x This step converts MOFs materials into Ti / Zn-O x The material can combine the advantages of MOF with the advantages of oxides. The present invention synthesizes a metal organic framework of nano-polyhedral Ti / Zn by a solvothermal method, then reduces it with L-alanine to obtain a porous hollow cage-like Ti / Zn oxide assembled by nano-sheets, and finally calcines it in air to obtain a porous hollow cage-like Ti / Zn-O composed of nanoparticles. x Using it in toothpaste can not only increase the resistance of toothpaste and improve its effect of cleaning teeth, but also play an antibacterial role and help oral cleaning. x The specific surface area is large, which can absorb oral odor very well. When used in the subsequent toothpaste preparation process, it can play a good antibacterial and whitening effect. The high specific surface area combined with the subsequent mixed dry powder can synergistically play an anti-allergic and anti-caries role.

[0008] S4, prepare mixed dry powder: weigh 7-11g of Ti / Zn-O prepared in step S3 xMaterials, 3-5g of silicon dioxide, 4-6g of calcium carbonate, 3-7g of sodium lauryl sulfate, 0.5-0.8g of sodium fluoride, 1-1.5g of potassium nitrate, 2-4g of sorbitol and 3-5g of sodium dihydrogen phosphate are put into a ball mill, ball milled for 2-4h to obtain a mixed dry powder. The purpose of this step is to make the raw materials necessary for toothpaste mix evenly, to ensure that the later paste is fine and granular, and to help the toothbrush to clean teeth better when brushing teeth. In addition, the main anti-sensitivity mechanism of fluoride in this step is that fluoride ions and calcium salts in the hard tissue of the tooth form calcium fluorapatite, which can not only block the dentinal tubules or narrow the diameter of the dentinal tubules, but also promote the formation of secondary dentin and enamel remineralization, and the anti-sensitivity mechanism of potassium nitrate is to interfere with the conduction of dental pulp nerve media by releasing potassium ions, and the two cooperate with each other to reduce the incidence of tooth sensitivity.

[0009] S5, weigh the polyacrylamide of 12-19g, the sodium hydroxymethyl cellulose of 25-31g, the hydroxyethyl cellulose of 6-11g and the mixed dry powder prepared by 10-12g step S4 are put into beaker, then the mixed extract prepared by step S1 of 185-230mL and the deionized water of 95-110mL are added, put into water bath under stirring, temperature remains at 58 DEG C, stir 4h, after powder is completely dissolved and forms suspension, continue to add 21-32mL glycerine and 1-1.5mL glutaraldehyde, continue to stir 6-8h in magnetic stirring apparatus, the dispersed material is added in vacuum paste making machine, the vacuum pump of opening paste making machine starts to evacuate, after vacuum stirring 35min, close vacuum pump and vacuum paste making machine stirring, toothpaste is filled in hose, and the toothpaste of anti-sensitivity, anti-caries and whitening can be obtained by sealing with tail sealing machine. The addition of glycerine in this step can make paste keep certain wetness and soft fluidity. Glutaraldehyde molecules are very small and can penetrate into the hard tissue of the tooth very well, interfering with the flow of liquid in the dentinal tubules, and reacting with the enamel matrix protein to reduce the number of oxygen free radicals that penetrate. In addition, glutaraldehyde combines with the protein components of the liquid in the dentinal tubules, causing them to denature and coagulate, thereby blocking the dentinal tubules, directly affecting the pathways for oxygen free radicals to stimulate the dental pulp nerves, and achieving the effect of reducing tooth sensitivity. However, it has a pungent odor, and the amount used must be strictly controlled.

[0010] Preferably: in step S1, 30 g of shiitake mushrooms, 36 g of green tea, 3 g of mint leaves, 11 g of isatis root and 5 g of jasmine are weighed and mixed evenly, ground and mashed, and then 220 mL of deionized water is added, boiled 8 times, each time for 32 minutes, the filtrates are combined, and a mixed extract is obtained by distillation.

[0011] Preferably: in step S1, 55 g of shiitake mushrooms, 25 g of green tea, 4 g of mint leaves, 9 g of isatis root and 6 g of jasmine are weighed and mixed evenly, ground and mashed, and then 220 mL of deionized water is added, boiled 8 times, each time for 32 minutes, the filtrates are combined, and a mixed extract is obtained by distillation.

[0012] Preferably: in step S2, take an appropriate amount of molecular sieves in a crucible, put the crucible into a muffle furnace, and heat treat at 310°C for 5 hours. After cooling to room temperature, put the heat-treated molecular sieves into a DMF and methanol solution, fully absorb water, and obtain anhydrous DMF and anhydrous methanol; then weigh 0.45g of 2-aminoterephthalic acid in a 50mL polytetrafluoroethylene reactor, measure 6mL of anhydrous DMF and 11mL of anhydrous methanol and add them to the above reactor, then quickly add 0.4mL of tetraisopropyl titanate and 0.1g of zinc sulfate to the reactor, and stir it evenly. Put the polytetrafluoroethylene reactor into a stainless steel reactor jacket, and then put it into an electric constant temperature blast drying oven, and heat treat it at 180°C for 12 hours. After the reaction, the reactor was cooled to room temperature, centrifuged to remove the supernatant, the yellow precipitate was collected, and the yellow precipitate was washed 5 times with anhydrous DMF and anhydrous methanol respectively, centrifuged to remove the DMF and methanol solutions, the yellow precipitate was collected, and vacuum dried at 80°C for 9h to obtain a nano-polyhedral Ti / Zn metal organic framework.

[0013] Preferably: in step S2, take an appropriate amount of molecular sieves in a crucible, put the crucible into a muffle furnace, and heat treat at 330°C for 4.5 hours. After cooling to room temperature, put the heat-treated molecular sieves into a DMF and methanol solution, fully absorb water, and obtain anhydrous DMF and anhydrous methanol; then weigh 0.38g of 2-aminoterephthalic acid in a 50mL polytetrafluoroethylene reactor, measure 7mL of anhydrous DMF and 9mL of anhydrous methanol and add them to the above reactor, then quickly add 0.3mL of tetraisopropyl titanate and 0.14g of zinc sulfate to the reactor, and stir it evenly. Put the polytetrafluoroethylene reactor into a stainless steel reactor jacket, and then put it into an electric constant temperature blast drying oven, and heat treat it at 170°C for 16 hours. After the reaction, the reactor was cooled to room temperature, centrifuged to remove the supernatant, the yellow precipitate was collected, and the yellow precipitate was washed 4 times with anhydrous DMF and anhydrous methanol respectively, centrifuged to remove the DMF and methanol solutions, the yellow precipitate was collected, and vacuum dried at 77°C for 8 h to obtain a nano-polyhedral Ti / Zn metal organic framework.

[0014] Preferably: in the step S3, 0.13 g of the Ti / Zn metal organic framework prepared in the step S2 is weighed and placed in a 50 mL polytetrafluoroethylene reactor, 9 mL of anhydrous ethanol is measured and added to the reactor, and then 0.05 g of L-alanine is added to the reactor, and the mixture is stirred evenly. The polytetrafluoroethylene reactor is placed in a stainless steel reactor jacket, and then placed in an electric constant temperature blast drying oven and heated at 180° C. for 19 hours. After the reaction is completed, the reactor is cooled to room temperature, centrifuged to remove the supernatant, and a dark yellow precipitate is collected. The dark yellow precipitate is washed with anhydrous ethanol for 4 times, centrifuged to remove the ethanol solution, and the dark yellow precipitate is collected. The precipitate is vacuum dried at 69°C for 9 hours to obtain a porous hollow cage-like Ti / Zn oxide assembled by nanosheets. Then, 0.13 g of the porous hollow cage-like Ti / Zn oxide assembled by the nanosheets is weighed and spread in a ceramic ark, and the ceramic ark is placed in the middle part of the quartz tube of a tube furnace. In an air atmosphere, the tube furnace is set to heat up to 590°C at a heating rate of 5°C / min, and the temperature is kept for 38 minutes. After natural cooling, a porous hollow cage-like Ti / Zn-O composed of nanoparticles can be obtained. x .

[0015] Preferably: in the step S3, 0.16 g of the Ti / Zn metal organic framework prepared in the step S2 is weighed and placed in a 50 mL polytetrafluoroethylene reactor, 9 mL of anhydrous ethanol is measured and added to the reactor, and then 0.08 g of L-alanine is added to the reactor, and it is stirred evenly, the polytetrafluoroethylene reactor is placed in a stainless steel reactor jacket, and then placed in an electric constant temperature blast drying oven and heated at 190° C. for heat treatment for 20 hours. After the reaction is completed, the reactor is cooled to room temperature, centrifuged to remove the supernatant, and a dark yellow precipitate is collected. The dark yellow precipitate is washed with anhydrous ethanol for 4 times, centrifuged to remove the ethanol solution, and the dark yellow precipitate is collected and vacuum dried at 80°C for 9 hours to obtain a porous hollow cage-like Ti / Zn oxide assembled by nanosheets. Then, 0.05 g of the porous hollow cage-like Ti / Zn oxide assembled by the nanosheets is weighed and spread in a ceramic ark, and the ceramic ark is placed in the middle part of the quartz tube of a tube furnace. In an air atmosphere, the tube furnace is set to heat up to 620°C at a heating rate of 5°C / min, and the temperature is kept for 30 minutes. After natural cooling, a porous hollow cage-like Ti / Zn-O composed of nanoparticles can be obtained. x .

[0016] Preferably: in step S4, 9 g of Ti / Zn-O prepared in step S3 is weighed. xMaterials, 4g of silicon dioxide, 5g of calcium carbonate, 6g of sodium lauryl sulfate, 0.7g of sodium fluoride, 1.5g of potassium nitrate, 4g of sorbitol and 3g of sodium dihydrogen phosphate are put into a ball mill, ball milled for 2h to obtain a mixed dry powder. The purpose of this step is to make the raw materials necessary for toothpaste mix evenly, to ensure that the later paste is fine and granular, and to help the toothbrush to clean teeth better when brushing teeth. In addition, in this step, the main anti-sensitivity mechanism of fluoride is that fluoride ions and calcium salts in the hard tissue of the tooth form calcium fluorapatite, which can not only block dentinal tubules or narrow the diameter of dentinal tubules, but also promote the formation of secondary dentin and enamel remineralization, and the anti-sensitivity mechanism of potassium nitrate is to interfere with the conduction of dental pulp nerve media by releasing potassium ions, and the two cooperate with each other to reduce the incidence of tooth sensitivity.

[0017] Preferably: in the step S5, 19g of polyacrylamide, 25g of sodium hydroxymethylcellulose, 11g of hydroxyethyl cellulose and 10g of the mixed dry powder prepared in step S4 are weighed and put into a beaker, then 230mL of the mixed extract prepared in step S1 and 95mL of deionized water are added, and the mixture is put into a water bath under stirring, and the temperature is always maintained at 58°C, and stirred for 4h. After the powder is completely dissolved and a suspension is formed, 32mL of glycerol and 1.5mL of glutaraldehyde are added, and the mixture is continuously stirred for 6h in a magnetic stirrer, and the dispersed materials are added to a vacuum paste making machine, and the vacuum pump of the paste making machine is turned on to start vacuuming. After vacuum stirring for 35min, the vacuum pump and the vacuum paste making machine are turned off and stirred, and the toothpaste is filled into a hose, and the toothpaste is sealed with a tail sealing machine to obtain an anti-allergic, anti-caries and whitening toothpaste. The addition of glycerol in this step can keep the paste in a certain degree of wetness and soft fluidity. Glutaraldehyde molecules are very small and can penetrate into the hard tissue of the tooth very well, interfering with the flow of liquid in the dentinal tubules, and reacting with the enamel matrix protein to reduce the number of oxygen free radicals that penetrate. In addition, glutaraldehyde combines with the protein components of the liquid in the dentinal tubules, causing them to denature and coagulate, thereby blocking the dentinal tubules, directly affecting the pathways for oxygen free radicals to stimulate the dental pulp nerves, and achieving the effect of reducing tooth sensitivity. However, it has a pungent odor, and the amount used must be strictly controlled.

[0018] The invention is beneficial in that:

[0019] 1. Ti / Zn-O used in preparing toothpaste or pharmaceutical composition of the present invention x It can not only increase the resistance of toothpaste and improve its effect in cleaning teeth, but also have an antibacterial effect and help oral cleaning.

[0020] 2. The present invention uses the Ti / Zn-O metal organic framework to prepare the Ti / Zn xThe specific surface area is large, which can absorb oral odor very well. When used in the subsequent toothpaste preparation process, it can play a good antibacterial and whitening effect. The high specific surface area combined with the subsequent mixed dry powder can synergistically play an anti-allergic and anti-caries role.

[0021] 3. The mixed extract used for preparing toothpaste or pharmaceutical composition of the present invention contains a large amount of fluoride, which has a strong antioxidant capacity and can be combined with apatite in teeth to have the effect of acid resistance and tooth decay prevention.

[0022] 4. The toothpaste or medicinal composition prepared by the present invention contains catechins which can reduce the presence of Streptococcus mutans, slow down tooth decay, and remove bad breath.

[0023] 5. In the mixed extract used to prepare the toothpaste or medicinal composition of the present invention, shiitake mushrooms, green tea, mint leaves, isatis root and jasmine complement each other and have a certain inhibitory effect on different bacteria in the oral cavity, which can better achieve the effect of anti-sensitivity and anti-caries.

[0024] 6. The toothpaste prepared by the present invention is fine and bright, has a refreshing smell and moderate viscosity, and the preparation process is stable and feasible.

[0025] 7. The present invention is simple to operate, has low production cost, and is conducive to mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The porous hollow cage-shaped Ti / Zn-O nanoparticles prepared in Example 1 of the present invention are x Scanning electron microscope image SEM.

[0027] Figure 2 The porous hollow cage-shaped Ti / Zn-O nanoparticles prepared in Example 1 of the present invention are x Transmission electron microscopy (TEM).

[0028] Figure 3 The porous hollow cage-shaped Ti / Zn-O nanoparticles prepared in Example 2 of the present invention are x Transmission electron microscopy and surface scanning energy spectrum.

[0029] Figure 4 This is a scanning electron microscope (SEM) image of TiO2 prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.

[0031] Example 1

[0032] S1, prepare mixed extract: weigh 30g of shiitake mushroom, 18g of green tea, 3g of mint leaves, 8g of isatis root and 5g of jasmine, mix them evenly, grind and mash them, add 220mL of deionized water, decoct 8 times, 32min each time, combine the filtrate, and obtain mixed extract by distillation. The green tea extract in this step contains a large amount of fluorine, has a strong antioxidant capacity, can be combined with apatite in teeth, and has the effect of acid resistance and tooth decay prevention. In addition, the catechins in green tea can reduce the presence of mutans streptococci, slow down tooth decay, and remove bad breath. The shiitake polysaccharides contained in shiitake mushrooms help prevent bacteria in the mouth from making dental plaque. In the mixed extract, shiitake mushrooms, green tea, mint leaves, isatis root and jasmine complement each other, have a certain inhibitory effect on different bacteria in the oral cavity, and can better achieve the effect of anti-sensitivity and tooth decay prevention.

[0033] S2. Take an appropriate amount of molecular sieves in a crucible, put the crucible into a muffle furnace, and heat treat at 310°C for 4 hours. After cooling to room temperature, put the heat-treated molecular sieves into DMF and methanol solution, fully absorb water, and obtain anhydrous DMF and anhydrous methanol; then weigh 0.3g of 2-aminoterephthalic acid in a 50mL polytetrafluoroethylene reactor, measure 6mL of anhydrous DMF and 8mL of anhydrous methanol and add them to the above reactor, then quickly add 0.2mL of tetraisopropyl titanate and 0.1g of zinc sulfate to the reactor, and stir it evenly. Put the polytetrafluoroethylene reactor into a stainless steel reactor sleeve, and then put it into an electric constant temperature blast drying oven, and heat treat it at 150°C for 12 hours. After the reaction, the reactor was cooled to room temperature, centrifuged to remove the supernatant, the yellow precipitate was collected, and the yellow precipitate was washed three times with anhydrous DMF and anhydrous methanol respectively, centrifuged to remove the DMF and methanol solutions, the yellow precipitate was collected, and vacuum dried at 60°C for 6 h to obtain a nano-polyhedral Ti / Zn metal organic framework.

[0034] S3. Weigh 0.05 g of the Ti / Zn metal organic framework prepared in step S2 and place it in a 50 mL polytetrafluoroethylene reactor. 8 mL of anhydrous ethanol is added to the reactor. Then, 0.05 g of L-alanine is added to the reactor and stirred evenly. The polytetrafluoroethylene reactor is placed in a stainless steel reactor jacket and then placed in an electric constant temperature forced air drying oven and heated at 180° C. for 18 h. After the reaction is completed, the reactor is cooled to room temperature, centrifuged to remove the supernatant, and a dark yellow precipitate is collected. The dark yellow precipitate is washed with anhydrous ethanol for 3 times, centrifuged to remove the ethanol solution, and the dark yellow precipitate is collected and vacuum dried at 60°C for 8h to obtain a porous hollow cage-like Ti / Zn oxide assembled by nanosheets. Then, 0.05g of the porous hollow cage-like Ti / Zn oxide assembled by the nanosheets is weighed and spread in a ceramic ark, and the ceramic ark is placed in the middle part of the quartz tube of a tube furnace. In an air atmosphere, the tube furnace is set to heat up to 580°C at a heating rate of 5°C / min, and the temperature is kept for 30min. After natural cooling, a porous hollow cage-like Ti / Zn-O composed of nanoparticles can be obtained. x This step converts MOFs materials into Ti / Zn-O x The material can combine the advantages of MOF with the advantages of oxides. The present invention synthesizes a metal organic framework of nano-polyhedral Ti / Zn by a solvothermal method, then reduces it with L-alanine to obtain a porous hollow cage-like Ti / Zn oxide assembled by nano-sheets, and finally calcines it in air to obtain a porous hollow cage-like Ti / Zn-O composed of nanoparticles. x Using it in toothpaste can not only increase the resistance of toothpaste and improve its effect of cleaning teeth, but also play an antibacterial role and help oral cleaning. x The specific surface area is large, which can absorb oral odor very well. When used in the subsequent toothpaste preparation process, it can play a good antibacterial and whitening effect. The high specific surface area combined with the subsequent mixed dry powder can synergistically play an anti-allergic and anti-caries role.

[0035] S4, prepare mixed dry powder: weigh 7g Ti / Zn-O prepared in step S3 xMaterials, 3g of silicon dioxide, 4g of calcium carbonate, 3g of sodium lauryl sulfate, 0.5g of sodium fluoride, 1g of potassium nitrate, 2g of sorbitol and 3g of sodium dihydrogen phosphate are put into a ball mill, ball milled for 2h to obtain a mixed dry powder. The purpose of this step is to make the raw materials necessary for toothpaste mix evenly, to ensure that the later paste is fine and granular, and to help the toothbrush to clean teeth better when brushing teeth. In addition, in this step, the main anti-sensitivity mechanism of fluoride is that fluoride ions and calcium salts in the hard tissue of the tooth form calcium fluorapatite, which can not only block the dentinal tubules or narrow the diameter of the dentinal tubules, but also promote the formation of secondary dentin and enamel remineralization, and the anti-sensitivity mechanism of potassium nitrate is to interfere with the conduction of dental pulp nerve media by releasing potassium ions, and the two cooperate with each other to reduce the incidence of tooth sensitivity.

[0036] S5, weigh the polyacrylamide of 12g, the sodium hydroxymethyl cellulose of 25g, the hydroxyethyl cellulose of 6g and the mixed dry powder prepared by 10g step S4 are put into beaker, then add the mixed extract prepared by step S1 of 185mL and the deionized water of 95mL, put into water bath under stirring, temperature remains at 58 DEG C, stir 4h, after powder is completely dissolved and forms suspension, continue to add 21mL glycerine and 1mL glutaraldehyde, continue to stir 6h in magnetic stirring apparatus, the dispersed material is added in vacuum paste making machine, open the vacuum pump of paste making machine and start to vacuumize, after vacuum stirring 35min, close vacuum pump and vacuum paste making machine and stir, paste is filled in hose, and toothpaste or medicinal composition of anti-sensitivity, anti-caries and whitening can be obtained with tail sealing machine. The addition of glycerine in this step can make paste keep certain wetness and soft fluidity. Glutaraldehyde molecules are very small and can penetrate into the hard tissue of the tooth very well, interfering with the flow of liquid in the dentinal tubules, and reacting with the enamel matrix protein to reduce the number of oxygen free radicals that penetrate. In addition, glutaraldehyde combines with the protein components of the liquid in the dentinal tubules, causing them to denature and coagulate, thereby blocking the dentinal tubules, directly affecting the pathways for oxygen free radicals to stimulate the dental pulp nerves, and achieving the effect of reducing tooth sensitivity. However, it has a pungent odor, and the amount used must be strictly controlled.

[0037] Figure 1 The porous hollow cage-shaped Ti / Zn-O nanoparticles prepared in Example 1 of the present invention are x Scanning electron microscope image SEM. Figure 2 The porous hollow cage-shaped Ti / Zn-O nanoparticles prepared in Example 1 of the present invention are x Transmission electron microscopy TEM. Figure 1 and Figure 2 It can be seen from the combination that the Ti / Zn-O xIt is a regular porous hollow cage structure. The nanoparticles have a large specific surface area and can absorb oral odor very well. Using them in toothpaste can not only increase the resistance of toothpaste and improve its effect of cleaning teeth, but also play an antibacterial role and help oral cleaning. x It also has antibacterial and whitening effects. When mixed with dry powder in toothpaste, it can synergistically play an anti-allergic and anti-caries role.

[0038] Non-toxic experimental verification: In the present invention, the porous hollow cage-shaped Ti / Zn-O x Prepare suspensions with concentrations of 15% and 8%, and store the prepared solutions in a refrigerator, requiring the refrigerator temperature to be controlled at 0-4°C. During the experiment, the method of gavage administration was selected, and drugs of different concentrations were gavaged to the experimental subjects according to equal volumes. The subjects selected by the present invention were 30 rats, with a body weight of 90-100g and an age of 5-7 weeks. The specific operation method is as follows: ① Group the experimental mice, select 30 mice to carry out acute toxicity tests, and divide them into a control group, experimental group 1 and experimental group 2 according to the random grouping method. The control group did not use drugs, and experimental group 1 was treated with a concentration of 15% Ti / Zn-O x Suspension, Experimental Group 2 used 8% Ti / Zn-O x ② The three groups of rats were fasted and deprived of water for 10 hours. ③ The experimental group was fed with Ti / Zn-O x suspension. The control group was fed with negative ion water, and the volume fed was the same as the drug volume of the experimental group. ④ Observation was carried out. Within the same day, not only the appearance and behavioral activities of the rats were observed, but also their breathing, secretions, defecation, etc. were recorded. All rats were fed for 7 days and their body weight was weighed. In addition, the time of death and toxic and side effects of the rats were recorded. ⑤ After the experiment, the pathological conditions of the organ tissues of the rats were observed, and the calculation and recording of the maximum tolerated dose were completed. In Experiment 1 of the present invention, oral administration was performed according to the requirements of maximum concentration and maximum volume. The drug concentration and solvent were 23% and 0.2mL / 20g, respectively. After 7 consecutive days of observation, there was no abnormality in the appearance and behavioral activities of the rats. At the same time, there was no significant difference in water intake, eating, breathing, secretions, and defecation from usual times. There was no death in the experimental rats. During continuous weighing, the body weight of the rats changed. Before administration, the body weight of rats in the control group was (92.34±1.16) g, the body weight of rats in the experimental group 1 was (91.92±2.13) g, and the body weight of rats in the experimental group 2 was (93.04±1.02) g. After 12 weeks of acute toxicity test, the average body weights of rats in the control group, experimental group 1, and experimental group 2 were (214.72±38.46) g, (221.21±37.52) g, and (218.33±36.52) g, respectively, with no statistically significant difference.x It is relatively safe. Combined with the dissection results of the later stage of the experiment, it can be seen that the Ti / Zn-O prepared by the present invention x After the treatment, no significant difference was found in the rats' heart, liver, kidney and other organs. x It is non-toxic and can be used in toothpaste.

[0039] Example 2

[0040] S1, prepare mixed extract: weigh 55g of shiitake mushroom, 36g of green tea, 5g of mint leaves, 11g of isatis root and 7g of jasmine, mix them evenly, grind and mash them, add 220mL of deionized water, decoct 8 times, 32min each time, combine the filtrate, and obtain mixed extract by distillation. The green tea extract in this step contains a large amount of fluorine, has a strong antioxidant capacity, can be combined with apatite in teeth, and has the effect of acid resistance and tooth decay prevention. In addition, the catechins in green tea can reduce the presence of mutans streptococci, slow down tooth decay, and remove bad breath. The shiitake polysaccharides contained in shiitake mushrooms help prevent bacteria in the mouth from producing dental plaque. In the mixed extract, shiitake mushrooms, green tea, mint leaves, isatis root and jasmine complement each other, have a certain inhibitory effect on different bacteria in the oral cavity, and can better achieve the effect of anti-sensitivity and tooth decay prevention.

[0041] S2. Take an appropriate amount of molecular sieves in a crucible, put the crucible into a muffle furnace, and heat treat at 350°C for 5h. After cooling to room temperature, put the heat-treated molecular sieves into DMF and methanol solution, fully absorb water, and obtain anhydrous DMF and anhydrous methanol; then weigh 0.45g of 2-aminoterephthalic acid in a 50mL polytetrafluoroethylene reactor, measure 8mL of anhydrous DMF and 11mL of anhydrous methanol and add them to the above reactor, then quickly add 0.4mL of tetraisopropyl titanate and 0.25g of zinc sulfate to the reactor, and stir it evenly. Put the polytetrafluoroethylene reactor into a stainless steel reactor sleeve, and then put it into an electric constant temperature blast drying oven, and heat treat it at 180°C for 18h. After the reaction, the reactor was cooled to room temperature, centrifuged to remove the supernatant, the yellow precipitate was collected, and the yellow precipitate was washed 5 times with anhydrous DMF and anhydrous methanol respectively, centrifuged to remove the DMF and methanol solutions, the yellow precipitate was collected, and vacuum dried at 80°C for 9h to obtain a nano-polyhedral Ti / Zn metal organic framework.

[0042] S3. Weigh 0.18 g of the Ti / Zn metal organic framework prepared in step S2 and place it in a 50 mL polytetrafluoroethylene reactor. Measure 11 mL of anhydrous ethanol and add it to the reactor. Then add 0.08 g of L-alanine to the reactor and stir it evenly. Place the polytetrafluoroethylene reactor in a stainless steel reactor jacket and then place it in an electric constant temperature forced air drying oven and heat it at 180°C for 22 hours. After the reaction is completed, the reactor is cooled to room temperature, centrifuged to remove the supernatant, and a dark yellow precipitate is collected. The dark yellow precipitate is washed with anhydrous ethanol for 3 times, centrifuged to remove the ethanol solution, and the dark yellow precipitate is collected and vacuum dried at 80°C for 10 hours to obtain a porous hollow cage-like Ti / Zn oxide assembled by nanosheets. Then, 0.13 g of the porous hollow cage-like Ti / Zn oxide assembled by the nanosheets is weighed and spread in a ceramic ark, and the ceramic ark is placed in the middle part of the quartz tube of a tube furnace. In an air atmosphere, the tube furnace is set to heat up to 620°C at a heating rate of 5°C / min, and the temperature is kept for 42 minutes. After natural cooling, a porous hollow cage-like Ti / Zn-O composed of nanoparticles can be obtained. x This step converts MOFs materials into Ti / Zn-O x The material can combine the advantages of MOF with the advantages of oxides. The present invention synthesizes a metal organic framework of nano-polyhedral Ti / Zn by a solvothermal method, then reduces it with L-alanine to obtain a porous hollow cage-like Ti / Zn oxide assembled by nano-sheets, and finally calcines it in air to obtain a porous hollow cage-like Ti / Zn-O composed of nanoparticles. x Using it in toothpaste can not only increase the resistance of toothpaste and improve its effect of cleaning teeth, but also play an antibacterial role and help oral cleaning. x The specific surface area is large, which can absorb oral odor very well. When used in the subsequent toothpaste preparation process, it can play a good antibacterial and whitening effect. The high specific surface area combined with the subsequent mixed dry powder can synergistically play an anti-allergic and anti-caries role.

[0043] S4. Prepare mixed dry powder: weigh 11 g of Ti / Zn-O prepared in step S3. xMaterials, 5g of silicon dioxide, 6g of calcium carbonate, 7g of sodium lauryl sulfate, 0.8g of sodium fluoride, 1.5g of potassium nitrate, 4g of sorbitol and 5g of sodium dihydrogen phosphate are put into a ball mill, ball milled for 4h to obtain a mixed dry powder. The purpose of this step is to make the raw materials necessary for toothpaste mix evenly, to ensure that the later paste is fine and granular, and to help the toothbrush to clean teeth better when brushing teeth. In addition, in this step, the main anti-sensitivity mechanism of fluoride is that fluoride ions and calcium salts in the hard tissue of the tooth form calcium fluorapatite, which can not only block the dentinal tubules or narrow the diameter of the dentinal tubules, but also promote the formation of secondary dentin and enamel remineralization, and the anti-sensitivity mechanism of potassium nitrate is to interfere with the conduction of dental pulp nerve media by releasing potassium ions, and the two cooperate with each other to reduce the incidence of tooth sensitivity.

[0044] S5, weigh the polyacrylamide of 19g, the sodium hydroxymethyl cellulose of 31g, the hydroxyethyl cellulose of 11g and the mixed dry powder prepared by 12g step S4 are put into beaker, then add the mixed extract prepared by step S1 of 230mL and the deionized water of 110mL, put into water bath under stirring, temperature remains at 58 DEG C, stir 4h, after powder is completely dissolved and forms suspension, continue to add 32mL glycerine and 1.5mL glutaraldehyde, continue to stir 8h in magnetic stirring apparatus, the dispersed material is added in vacuum paste making machine, open the vacuum pump of paste making machine and start to evacuate, after vacuum stirring 35min, close vacuum pump and vacuum paste making machine and stir, toothpaste is filled in hose, and the toothpaste of anti-sensitivity, anti-caries and whitening can be obtained by sealing with tail sealing machine. The addition of glycerine in this step can make paste keep certain wetness and soft fluidity. Glutaraldehyde molecules are very small and can penetrate into the hard tissue of the tooth very well, interfering with the flow of liquid in the dentinal tubules, and reacting with the enamel matrix protein to reduce the number of oxygen free radicals that penetrate. In addition, glutaraldehyde combines with the protein components of the liquid in the dentinal tubules, causing them to denature and coagulate, thereby blocking the dentinal tubules, directly affecting the pathways for oxygen free radicals to stimulate the dental pulp nerves, and achieving the effect of reducing tooth sensitivity. However, it has a pungent odor, and the amount used must be strictly controlled.

[0045] Comparative Example 1: In step S1, except that 0.25 g of zinc sulfate is not added in step S2, the remaining steps are the same as those in Example 2.

[0046] Figure 3 The transmission electron microscope image and surface scanning energy spectrum of the porous hollow cage-shaped Ti / Zn-Ox composed of nanoparticles prepared in Example 2 of the present invention. It can be clearly seen from the surface scanning distribution diagram of the transmission electron microscope that Ti, Zn and O elements are uniformly distributed in the porous hollow cage-shaped Ti / Zn-O x On top. Figure 4This is a scanning electron microscope image SEM of TiO2 prepared in comparative example 1 of the present invention. It can be seen from the figure that the hollowness of the bulk of Zn-doped TiO2 is much lower than that of the porous hollow cage-like Ti / Zn-O2 composed of nanoparticles prepared in Example 2 of the present invention. x , which is not conducive to the adsorption of stains on teeth, and without the synergistic effect of Zn and Ti, the antibacterial effect is greatly weakened.

[0047] Example 3

[0048] S1, prepare mixed extract: weigh 40g of shiitake mushroom, 30g of green tea, 4g of mint leaves, 9g of isatis root and 6g of jasmine, mix them evenly, grind and mash them, add 220mL of deionized water, decoct 8 times, 32min each time, combine the filtrate, and obtain mixed extract by distillation. The green tea extract in this step contains a large amount of fluorine, has a strong antioxidant capacity, can be combined with apatite in teeth, and has the effect of acid resistance and tooth decay prevention. In addition, the catechins in green tea can reduce the presence of mutans streptococci, slow down tooth decay, and remove bad breath. The shiitake polysaccharides contained in shiitake mushrooms help prevent bacteria in the mouth from producing dental plaque. In the mixed extract, shiitake mushrooms, green tea, mint leaves, isatis root and jasmine complement each other, have a certain inhibitory effect on different bacteria in the oral cavity, and can better achieve the effect of anti-sensitivity and tooth decay prevention.

[0049] S2. Take an appropriate amount of molecular sieves in a crucible, put the crucible into a muffle furnace, and heat treat at 320°C for 4.2 hours. After cooling to room temperature, put the heat-treated molecular sieves into DMF and methanol solution, fully absorb water, and obtain anhydrous DMF and anhydrous methanol; then weigh 0.37g of 2-aminoterephthalic acid in a 50mL polytetrafluoroethylene reactor, measure 7mL of anhydrous DMF and 9mL of anhydrous methanol and add them to the above reactor, then quickly add 0.3mL of tetraisopropyl titanate and 0.15g of zinc sulfate to the reactor, and stir it evenly. Put the polytetrafluoroethylene reactor into a stainless steel reactor sleeve, and then put it into an electric constant temperature blast drying oven, and heat treat it at 170°C for 16 hours. After the reaction, the reactor was cooled to room temperature, centrifuged to remove the supernatant, the yellow precipitate was collected, and the yellow precipitate was washed 4 times with anhydrous DMF and anhydrous methanol respectively, centrifuged to remove the DMF and methanol solutions, the yellow precipitate was collected, and vacuum dried at 75°C for 8 h to obtain a nano-polyhedral Ti / Zn metal organic framework.

[0050] S3. Weigh 0.08 g of the Ti / Zn metal organic framework prepared in step S2 and place it in a 50 mL polytetrafluoroethylene reactor. Measure 9 mL of anhydrous ethanol and add it to the reactor. Then add 0.07 g of L-alanine to the reactor and stir it evenly. Place the polytetrafluoroethylene reactor in a stainless steel reactor jacket and then place it in an electric constant temperature forced air drying oven and heat it at 185° C. for 20 h. After the reaction is completed, the reactor is cooled to room temperature, centrifuged to remove the supernatant, and a dark yellow precipitate is collected. The dark yellow precipitate is washed with anhydrous ethanol for 4 times, centrifuged to remove the ethanol solution, and the dark yellow precipitate is collected and vacuum dried at 75°C for 9 hours to obtain a porous hollow cage-like Ti / Zn oxide assembled by nanosheets. Then, 0.08 g of the porous hollow cage-like Ti / Zn oxide assembled by the nanosheets is weighed and spread in a ceramic ark, and the ceramic ark is placed in the middle part of the quartz tube of a tube furnace. In an air atmosphere, the tube furnace is set to heat up to 595°C at a heating rate of 5°C / min, and the temperature is kept for 35 minutes. After natural cooling, a porous hollow cage-like Ti / Zn-O composed of nanoparticles can be obtained. x This step converts MOFs materials into Ti / Zn-O x The material can combine the advantages of MOF with the advantages of oxides. The present invention synthesizes a metal organic framework of nano-polyhedral Ti / Zn by a solvothermal method, then reduces it with L-alanine to obtain a porous hollow cage-like Ti / Zn oxide assembled by nano-sheets, and finally calcines it in air to obtain a porous hollow cage-like Ti / Zn-O composed of nanoparticles. x Using it in toothpaste can not only increase the resistance of toothpaste and improve its effect of cleaning teeth, but also play an antibacterial role and help oral cleaning. x The specific surface area is large, which can absorb oral odor very well. When used in the subsequent toothpaste preparation process, it can play a good antibacterial and whitening effect. The high specific surface area combined with the subsequent mixed dry powder can synergistically play an anti-allergic and anti-caries role.

[0051] S4, prepare mixed dry powder: weigh 8g of Ti / Zn-O prepared in step S3 xMaterials, 4g of silicon dioxide, 5g of calcium carbonate, 6g of sodium lauryl sulfate, 0.7g of sodium fluoride, 1.2g of potassium nitrate, 3g of sorbitol and 4g of sodium dihydrogen phosphate are put into a ball mill, ball milled for 3h to obtain a mixed dry powder. The purpose of this step is to make the raw materials necessary for toothpaste mix evenly, to ensure that the later paste is fine and granular, and to help the toothbrush to clean teeth better when brushing teeth. In addition, in this step, the main anti-sensitivity mechanism of fluoride is that fluoride ions and calcium salts in the hard tissue of the tooth form calcium fluorapatite, which can not only block the dentinal tubules or narrow the diameter of the dentinal tubules, but also promote the formation of secondary dentin and enamel remineralization, and the anti-sensitivity mechanism of potassium nitrate is to interfere with the conduction of dental pulp nerve media by releasing potassium ions, and the two cooperate with each other to reduce the incidence of tooth sensitivity.

[0052] S5, weigh the polyacrylamide of 18g, the sodium hydroxymethyl cellulose of 29g, the hydroxyethyl cellulose of 9g and the mixed dry powder prepared by 11g step S4 are put into beaker, then add the mixed extract prepared by step S1 of 193mL and the deionized water of 105mL, put into water bath under stirring, temperature remains at 58 DEG C, stir 4h, after powder is completely dissolved and forms suspension, continue to add 28mL glycerine and 1.2mL glutaraldehyde, continue to stir 7h in magnetic stirring apparatus, the dispersed material is added in vacuum paste making machine, open the vacuum pump of paste making machine and start to evacuate, after vacuum stirring 35min, close vacuum pump and vacuum paste making machine and stir, toothpaste is filled in hose, and the toothpaste of anti-sensitivity, anti-caries and whitening can be obtained by sealing with tail sealing machine. The addition of glycerine in this step can make paste keep certain wetness and soft fluidity. Glutaraldehyde molecules are very small and can penetrate into the hard tissue of the tooth very well, interfering with the flow of liquid in the dentinal tubules, and reacting with the enamel matrix protein to reduce the number of oxygen free radicals that penetrate. In addition, glutaraldehyde combines with the protein components of the liquid in the dentinal tubules, causing them to denature and coagulate, thereby blocking the dentinal tubules, directly affecting the pathways for oxygen free radicals to stimulate the dental pulp nerves, and achieving the effect of reducing tooth sensitivity. However, it has a pungent odor, and the amount used must be strictly controlled.

[0053] Comparative Example 2: In step S1, except that 40 g of shiitake mushrooms and 30 g of green tea are not added, the remaining steps are the same as those of Example 3.

[0054] Comparative Example 3: In step S4, except that Ti / Zn-O x Except for potassium nitrate, the other steps are the same as those in Example 3.

[0055] The test strains of the present invention select different bacteria that are easy to appear in the oral cavity for testing, such as Staphylococcus aureus (ATCC 6538), Escherichia coli (ATCC 25922), Candida albicans (ATCC 10231), Porphyromonas gingivalis (ATCC 33277), and Streptococcus mutans (ATCC 25175). The test is carried out with reference to QB / T2738-2012 Section 7.3, and the antibacterial rate of the sample after the toothpaste is diluted 4 times and 90 times with deionized water is tested respectively, the action time is 10 minutes, the test is repeated 5 times, and the average value is taken.

[0056] Table 1

[0057] Example 3 Staphylococcus aureus Escherichia coli Candida albicans Porphyromonas gingivalis Streptococcus mutans Antibacterial rate after 4-fold dilution (%) >99 >99 >99 >99 >99 Antibacterial rate after 90-fold dilution (%) 96 83 86 65 54

[0058] Table 2

[0059] Comparative Example 1 Staphylococcus aureus Escherichia coli Candida albicans Porphyromonas gingivalis Streptococcus mutans Antibacterial rate after 4-fold dilution (%) 92 88 89 68 74 Antibacterial rate after 90-fold dilution (%) 68 53 49 35 42

[0060] Table 3

[0061] Comparative Example 2 Staphylococcus aureus Escherichia coli Candida albicans Porphyromonas gingivalis Streptococcus mutans Antibacterial rate after 4-fold dilution (%) 91 76 69 77 85 Antibacterial rate after 90-fold dilution (%) 52 43 34 31 23

[0062] Table 4

[0063] Comparative Example 3 Staphylococcus aureus Escherichia coli Candida albicans Porphyromonas gingivalis Streptococcus mutans Antibacterial rate after 4-fold dilution (%) 88 69 82 62 67 Antibacterial rate after 90-fold dilution (%) 35 39 41 27 35

[0064] From the experimental results in Tables 1-4, it can be seen that the toothpaste prepared in Example 3 and Comparative Example 1-3 has an antibacterial effect on Staphylococcus aureus, Escherichia coli, Candida albicans, Porphyromonas gingivalis, and Streptococcus mutans after being diluted 4 times and 90 times, indicating that the toothpaste prepared in Example 3 has the best antibacterial effect. Example 3 and Comparative Example 1 illustrate that the antibacterial effect of Ti / Zn-O x There is a synergistic effect between Zn and Ti in the material, which has a certain inhibitory effect on different bacteria in the oral cavity, and can better achieve the effect of anti-sensitivity and anti-caries. The comparison of the antibacterial effect of toothpaste prepared by Example 3 and Comparative Examples 2 and 3 shows that the mixed extract prepared by the present invention contains a large amount of fluorine, has a strong antioxidant capacity, can be combined with apatite in teeth, and has the effect of acid resistance and anti-caries. In addition, the catechins in green tea can reduce the presence of Streptococcus mutans, slow down tooth decay, and remove bad breath. The shiitake polysaccharides contained in shiitake mushrooms help prevent bacteria in the mouth from making dental plaque. Shiitake mushrooms, green tea, mint leaves, isatis root and jasmine in the mixed extract complement each other, have a certain inhibitory effect on different bacteria in the oral cavity, and can better achieve the effect of anti-sensitivity and anti-caries.

[0065] Example 4

[0066] S1, prepare mixed extract: weigh 45g of shiitake mushroom, 25g of green tea, 4g of mint leaves, 9g of isatis root and 6g of jasmine, mix them evenly, grind and mash them, add 220mL of deionized water, decoct 8 times, 32min each time, combine the filtrate, and obtain mixed extract by distillation. The green tea extract in this step contains a large amount of fluorine, has a strong antioxidant capacity, can be combined with apatite in teeth, and has the effect of acid resistance and tooth decay prevention. In addition, the catechins in green tea can reduce the presence of mutans streptococci, slow down tooth decay, and remove bad breath. The shiitake polysaccharides contained in shiitake mushrooms help prevent bacteria in the mouth from producing dental plaque. In the mixed extract, shiitake mushrooms, green tea, mint leaves, isatis root and jasmine complement each other, have a certain inhibitory effect on different bacteria in the oral cavity, and can better achieve the effect of anti-sensitivity and tooth decay prevention.

[0067] S2. Take an appropriate amount of molecular sieves in a crucible, put the crucible into a muffle furnace, and heat treat at 332°C for 4.2 hours. After cooling to room temperature, put the heat-treated molecular sieves into DMF and methanol solution, fully absorb water, and obtain anhydrous DMF and anhydrous methanol; then weigh 0.38g of 2-aminoterephthalic acid in a 50mL polytetrafluoroethylene reactor, measure 7mL of anhydrous DMF and 9mL of anhydrous methanol and add them to the above reactor, then quickly add 0.3mL of tetraisopropyl titanate and 0.17g of zinc sulfate to the reactor, and stir it evenly. Put the polytetrafluoroethylene reactor into a stainless steel reactor jacket, and then put it into an electric constant temperature blast drying oven, and heat treat it at 170°C for 16 hours. After the reaction, the reactor was cooled to room temperature, centrifuged to remove the supernatant, the yellow precipitate was collected, and the yellow precipitate was washed 4 times with anhydrous DMF and anhydrous methanol respectively, centrifuged to remove the DMF and methanol solutions, the yellow precipitate was collected, and vacuum dried at 74°C for 8 h to obtain a nano-polyhedral Ti / Zn metal organic framework.

[0068] S3. Weigh 0.09 g of the Ti / Zn metal organic framework prepared in step S2 and place it in a 50 mL polytetrafluoroethylene reactor. Measure 8-11 mL of anhydrous ethanol and add it to the reactor. Then add 0.07 g of L-alanine to the reactor and stir it evenly. Place the polytetrafluoroethylene reactor in a stainless steel reactor jacket and then place it in an electric constant temperature forced air drying oven and heat it at 185° C. for 21 hours. After the reaction is completed, the reactor is cooled to room temperature, centrifuged to remove the supernatant, and a dark yellow precipitate is collected. The dark yellow precipitate is washed with anhydrous ethanol for 4 times, centrifuged to remove the ethanol solution, and the dark yellow precipitate is collected and vacuum dried at 66°C for 9 hours to obtain a porous hollow cage-like Ti / Zn oxide assembled by nanosheets; then 0.08 g of the porous hollow cage-like Ti / Zn oxide assembled by the nanosheets is weighed and spread in a ceramic ark, and the ceramic ark is placed in the middle part of the quartz tube of a tube furnace. In an air atmosphere, the tube furnace is set to heat up to 585°C at a heating rate of 5°C / min, and the temperature is kept for 30 minutes. After natural cooling, a porous hollow cage-like Ti / Zn-O composed of nanoparticles can be obtained. x This step converts MOFs materials into Ti / Zn-O x The material can combine the advantages of MOF with the advantages of oxides. The present invention synthesizes a metal organic framework of nano-polyhedral Ti / Zn by a solvothermal method, then reduces it with L-alanine to obtain a porous hollow cage-like Ti / Zn oxide assembled by nano-sheets, and finally calcines it in air to obtain a porous hollow cage-like Ti / Zn-O composed of nanoparticles. x Using it in toothpaste can not only increase the resistance of toothpaste and improve its effect of cleaning teeth, but also play an antibacterial role and help oral cleaning. x The specific surface area is large, which can absorb oral odor very well. When used in the subsequent toothpaste preparation process, it can play a good antibacterial and whitening effect. The high specific surface area combined with the subsequent mixed dry powder can synergistically play an anti-allergic and anti-caries role.

[0069] S4, prepare mixed dry powder: weigh 10g Ti / Zn-O prepared in step S3 xMaterials, 4g of silicon dioxide, 5g of calcium carbonate, 6g of sodium lauryl sulfate, 0.6g of sodium fluoride, 1g of potassium nitrate, 3g of sorbitol and 4g of sodium dihydrogen phosphate are put into a ball mill, ball milled for 3h to obtain a mixed dry powder. The purpose of this step is to make the raw materials necessary for toothpaste mix evenly, to ensure that the later paste is fine and granular, and to help the toothbrush to clean teeth better when brushing teeth. In addition, in this step, the main anti-sensitivity mechanism of fluoride is that fluoride ions and calcium salts in the hard tissue of the tooth form calcium fluorapatite, which can not only block the dentinal tubules or narrow the diameter of the dentinal tubules, but also promote the formation of secondary dentin and enamel remineralization, and the anti-sensitivity mechanism of potassium nitrate is to interfere with the conduction of dental pulp nerve media by releasing potassium ions, and the two cooperate with each other to reduce the incidence of tooth sensitivity.

[0070] S5, weigh the polyacrylamide of 17g, the sodium hydroxymethyl cellulose of 28g, the hydroxyethyl cellulose of 7g and the mixed dry powder prepared by 11g step S4 are put into beaker, then the mixed extract prepared by step S1 of 185mL and the deionized water of 95mL are added, put into water-bath under stirring, temperature remains at 58 DEG C, stir 4h, after powder is completely dissolved and forms suspension, continue to add 32mL glycerine and 1.5mL glutaraldehyde, continue to stir 8h in magnetic stirring apparatus, the dispersed material is added in vacuum paste making machine, the vacuum pump of paste making machine is opened and vacuum is started, after vacuum stirring 35min, vacuum pump is closed and vacuum paste making machine is stirred, toothpaste is filled in hose, and the toothpaste of anti-sensitivity, anti-caries and whitening can be obtained by tail sealing with tail sealing machine. The addition of glycerine in this step can make paste keep certain wetness and soft fluidity. Glutaraldehyde molecules are very small and can penetrate into the hard tissue of the tooth very well, interfering with the flow of liquid in the dentinal tubules, and reacting with the enamel matrix protein to reduce the number of oxygen free radicals that penetrate. In addition, glutaraldehyde combines with the protein components of the liquid in the dentinal tubules, causing them to denature and coagulate, thereby blocking the dentinal tubules, directly affecting the pathways for oxygen free radicals to stimulate the dental pulp nerves, and achieving the effect of reducing tooth sensitivity. However, it has a pungent odor, and the amount used must be strictly controlled.

[0071] Comparative Example 4: In step S4, except that Ti / Zn-O x Except for this, the remaining steps are the same as those in Example 4.

[0072] Comparative Example 5: In step S4, except that Ti / Zn-O x Except for this, the remaining steps are the same as those in Example 4.

[0073] The toothpaste friction value detection in the present invention: Because toothpaste contains solid abrasives, long-term use of toothpaste with a high friction value can clean teeth well, but it will also damage teeth and cause enamel loss. The greater the wear value, the higher the degree of wear on teeth. The present invention adopts the "Toothpaste Friction Value Test Method (GB / T35832-2018)" to test the friction value Ra of toothpaste. The smaller the friction value, the less wear the toothpaste has on teeth. When choosing toothpaste, you should choose products with high cleaning rate and low friction value.

[0074] Table 5. Ra value of toothpaste

[0075] toothpaste Example 4 Comparative Example 4 Comparative Example 5 Commercially available salt whitening toothpaste Ra 1.424±0.013 0.965±0.008 2.032±0.001 2.19±0.004

[0076] As shown in Table 5, Comparative Example 4 does not contain Ti / Zn-O x When the friction value is too small, it is not conducive to teeth cleaning and will not achieve the effect of teeth whitening. x The friction value of the prepared toothpaste is relatively large, which is similar to that of commercial toothpaste, and is beneficial to tooth damage and anti-sensitivity. x The introduction of increases the friction of the toothpaste, thereby enhancing the stain removal and whitening effect of the toothpaste. The high specific surface area and nanostructure make its friction value much lower than that of commercial toothpaste, and will not cause wear to the teeth. Therefore, the toothpaste prepared by the present invention can have a good effect of stain removal and tooth cleaning, and also has the effect of anti-sensitivity and anti-caries.

[0077] The above-mentioned embodiments only express the specific implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present invention. It should be pointed out that, for those skilled in the art, without departing from the concept of the present invention, any other changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A preparation process for an anti-allergic, anti-caries and whitening toothpaste, characterized in that: The specific preparation method is as follows: S1. Prepare a mixed extract: weigh 30-55g of shiitake mushrooms, 18-36g of green tea, 3-5g of mint leaves, 8-11g of isatis root and 5-7g of jasmine, mix them evenly, grind and mash them, add 220mL of deionized water, boil them for 8 times, each time for 32min, combine the filtrates, and obtain a mixed extract by distillation; S2. Take an appropriate amount of molecular sieves in a crucible, put the crucible into a muffle furnace, and heat treat at 310-350°C for 4-5h; after cooling to room temperature, put the heat-treated molecular sieves into N, N-dimethylformamide DMF and methanol solution to fully absorb water to obtain anhydrous DMF and anhydrous methanol; then weigh 0.3-0.45g of 2-aminoterephthalic acid and put it in a 50mL polytetrafluoroethylene reactor, measure 6-8mL of anhydrous DMF and 8-11mL of anhydrous methanol and add them to the above reactor, and then quickly add 0.2-0.4mL of titanic acid to the reactor. tetraisopropyl ester and 0.1-0.25g zinc sulfate, stir them evenly; put the polytetrafluoroethylene reactor into a stainless steel reactor jacket, and then put it into an electric constant temperature blast drying oven, and heat treat it at 150-180°C for 12-18h; after the reaction, wait for the reactor to cool to room temperature, centrifuge to remove the supernatant, collect the yellow precipitate, wash the yellow precipitate with anhydrous DMF and anhydrous methanol for 3-5 times respectively, centrifuge to remove the DMF and methanol solutions, collect the yellow precipitate, and vacuum dry it at 60-80°C for 6-9h to obtain a nano-polyhedral Ti / Zn metal organic framework; S3, weigh 0.05-0.18g of the Ti / Zn metal organic framework prepared in step S2 and place it in a 50mL polytetrafluoroethylene reactor, measure 8-11mL of anhydrous ethanol and add it to the reactor, then add 0.05-0.08g of L-alanine to the reactor, stir it evenly, put the polytetrafluoroethylene reactor into a stainless steel reactor sleeve, and then put it into an electric constant temperature blast drying oven and heat it at 180-190°C for 18-22h; after the reaction is completed, after the reactor is cooled to room temperature, centrifuge to remove the supernatant, collect the dark yellow precipitate, and wash the dark yellow precipitate with anhydrous ethanol for 3-5 times , centrifuge to remove the ethanol solution, collect the dark yellow precipitate, and vacuum dry it at 60-80°C for 8-10h to obtain a porous hollow cage-like Ti / Zn oxide assembled by nanosheets; then weigh 0.05-0.13g of the porous hollow cage-like Ti / Zn oxide assembled by the nanosheets and spread it in a ceramic ark, put the ceramic ark into the middle part of the quartz tube of a tube furnace, set the tube furnace to heat up to 580-620°C at a heating rate of 5°C / min in an air atmosphere, and keep it warm for 30-42min, and cool it naturally to obtain a porous hollow cage-like Ti / Zn-O x ; S4, prepare mixed dry powder: weigh 7-11g of Ti / Zn-O prepared in step S3 x , 3-5 g of silicon dioxide, 4-6 g of calcium carbonate, 3-7 g of sodium lauryl sulfate, 0.5-0.8 g of sodium fluoride, 1-1.5 g of potassium nitrate, 2-4 g of sorbitol and 3-5 g of sodium dihydrogen phosphate are put into a ball mill and ball milled for 2-4 hours to obtain a mixed dry powder; S5. Weigh 12-19g of polyacrylamide, 25-31g of sodium hydroxymethyl cellulose, 6-11g of hydroxyethyl cellulose and 10-12g of the mixed dry powder prepared in step S4 and put them into a beaker, then add 185-230mL of the mixed extract prepared in step S1 and 95-110mL of deionized water, put them into a water bath under stirring, keep the temperature at 58°C, stir for 4h, after the powder is completely dissolved and forms a suspension, continue to add 21-32mL of glycerol and 1-1.5mL of glutaraldehyde, continue to stir in a magnetic stirrer for 6-8h, add the dispersed materials into a vacuum paste making machine, turn on the vacuum pump of the paste making machine and start vacuuming, after vacuum stirring for 35min, turn off the vacuum pump and the vacuum paste making machine to stir, fill the toothpaste into a hose, and seal the tail with a tail sealing machine to obtain an anti-allergic, anti-caries and whitening toothpaste.

2. The preparation process of an anti-allergic, anti-caries and whitening toothpaste according to claim 1, characterized in that: In the step S1, 30 g of shiitake mushrooms, 36 g of green tea, 3 g of mint leaves, 11 g of isatis root and 5 g of jasmine are weighed and mixed evenly, ground and mashed, and then 220 mL of deionized water is added, and the mixture is decocted for 8 times, each time for 32 minutes, and the filtrates are combined and distilled to obtain a mixed extract.

3. The preparation process of an anti-allergic, anti-caries and whitening toothpaste according to claim 1 or 2, characterized in that: In the step S1, 55 g of shiitake mushrooms, 25 g of green tea, 4 g of mint leaves, 9 g of isatis root and 6 g of jasmine are weighed and mixed evenly, ground and mashed, and then 220 mL of deionized water is added, and the mixture is decocted for 8 times, each time for 32 minutes, and the filtrates are combined and distilled to obtain a mixed extract.

4. The preparation process of an anti-allergic, anti-caries and whitening toothpaste according to claim 2, characterized in that: In step S2, a proper amount of molecular sieve is placed in a crucible, the crucible is placed in a muffle furnace, and heat-treated at 310° C. for 5 h; after cooling to room temperature, the heat-treated molecular sieve is placed in a DMF and methanol solution to fully absorb water to obtain anhydrous DMF and anhydrous methanol; then 0.45 g of 2-aminoterephthalic acid is weighed in a 50 mL polytetrafluoroethylene reactor, 6 mL of anhydrous DMF and 11 mL of anhydrous methanol are measured and added to the reactor, and then 0.4 mL of tetraisopropyl titanate is quickly added to the reactor. and 0.1 g of zinc sulfate, stir them evenly; put the polytetrafluoroethylene reactor into a stainless steel reactor jacket, and then put it into an electric constant temperature forced air drying oven, and heat treat it at 180°C for 12 hours; after the reaction is completed, wait for the reactor to cool to room temperature, centrifuge to remove the supernatant, collect the yellow precipitate, wash the yellow precipitate with anhydrous DMF and anhydrous methanol for 5 times respectively, centrifuge to remove the DMF and methanol solutions, collect the yellow precipitate, and vacuum dry it at 80°C for 9 hours to obtain the metal organic framework of nano-polyhedron Ti / Zn.

5. The preparation process of an anti-allergic, anti-caries and whitening toothpaste according to claim 3, characterized in that: In step S2, a proper amount of molecular sieve is placed in a crucible, the crucible is placed in a muffle furnace, and heat-treated at 330° C. for 4.5 h; after cooling to room temperature, the heat-treated molecular sieve is placed in a DMF and methanol solution to fully absorb water to obtain anhydrous DMF and anhydrous methanol; then 0.38 g of 2-aminoterephthalic acid is weighed in a 50 mL polytetrafluoroethylene reactor, 7 mL of anhydrous DMF and 9 mL of anhydrous methanol are measured and added to the above reactor, and then 0.3 mL of tetraisopropyl titanate is quickly added to the reactor. and 0.14 g of zinc sulfate, stir them evenly; put the polytetrafluoroethylene reactor into a stainless steel reactor jacket, and then put it into an electric constant temperature forced air drying oven, and heat treat it at 170°C for 16 hours; after the reaction is completed, wait for the reactor to cool to room temperature, centrifuge to remove the supernatant, collect the yellow precipitate, wash the yellow precipitate with anhydrous DMF and anhydrous methanol for 4 times respectively, centrifuge to remove the DMF and methanol solutions, collect the yellow precipitate, and vacuum dry it at 77°C for 8 hours to obtain a nano-polyhedral Ti / Zn metal organic framework.

6. The preparation process of an anti-allergic, anti-caries and whitening toothpaste according to claim 4, characterized in that: In the step S3, 0.13 g of the Ti / Zn metal organic framework prepared in step S2 is weighed and placed in a 50 mL polytetrafluoroethylene reactor, 9 mL of anhydrous ethanol is measured and added to the reactor, and then 0.05 g of L-alanine is added to the reactor, and the mixture is stirred evenly. The polytetrafluoroethylene reactor is placed in a stainless steel reactor jacket, and then placed in an electric constant temperature blast drying oven and heated at 180° C. for 19 h; after the reaction is completed, the reactor is cooled to room temperature, centrifuged to remove the supernatant, a dark yellow precipitate is collected, and the dark yellow precipitate is washed 4 times with anhydrous ethanol. , centrifuge to remove the ethanol solution, collect the dark yellow precipitate, and vacuum dry it at 69°C for 9h to obtain a porous hollow cage-like Ti / Zn oxide assembled by nanosheets; then weigh 0.13g of the porous hollow cage-like Ti / Zn oxide assembled by nanosheets and spread it in a ceramic ark, put the ceramic ark into the middle part of the quartz tube of a tube furnace, set the tube furnace to heat up to 590°C at a heating rate of 5°C / min in an air atmosphere, and keep it warm for 38min. After natural cooling, a porous hollow cage-like Ti / Zn-O composed of nanoparticles can be obtained. x .

7. The preparation process of the anti-allergic, anti-caries and whitening toothpaste according to claim 5, characterized in that: In the step S3, 0.16 g of the Ti / Zn metal organic framework prepared in step S2 is weighed and placed in a 50 mL polytetrafluoroethylene reactor, 9 mL of anhydrous ethanol is measured and added to the reactor, and then 0.08 g of L-alanine is added to the reactor, and the mixture is stirred evenly. The polytetrafluoroethylene reactor is placed in a stainless steel reactor jacket, and then placed in an electric constant temperature blast drying oven and heated at 190° C. for 20 h; after the reaction is completed, the reactor is cooled to room temperature, centrifuged to remove the supernatant, a dark yellow precipitate is collected, and the dark yellow precipitate is washed 4 times with anhydrous ethanol. , centrifuge to remove the ethanol solution, collect the dark yellow precipitate, and vacuum dry it at 80°C for 9h to obtain a porous hollow cage-like Ti / Zn oxide assembled by nanosheets; then weigh 0.05g of the porous hollow cage-like Ti / Zn oxide assembled by nanosheets and spread it in a ceramic ark, put the ceramic ark into the middle part of the quartz tube of a tube furnace, set the tube furnace to heat up to 620°C at a heating rate of 5°C / min in an air atmosphere, and keep it warm for 30min. After natural cooling, a porous hollow cage-like Ti / Zn-O composed of nanoparticles can be obtained. x .

8. The preparation process of an anti-allergic, anti-caries and whitening toothpaste according to claim 6, characterized in that: In step S4, 9 g of Ti / Zn-O prepared in step S3 is weighed. x , 4 g of silicon dioxide, 5 g of calcium carbonate, 6 g of sodium lauryl sulfate, 0.7 g of sodium fluoride, 1.5 g of potassium nitrate, 4 g of sorbitol and 3 g of sodium dihydrogen phosphate were put into a ball mill and ball milled for 2 hours to obtain a mixed dry powder.

9. The preparation process of an anti-allergic, anti-caries and whitening toothpaste according to claim 7, characterized in that: In the step S5, 19 g of polyacrylamide, 25 g of sodium hydroxymethyl cellulose, 11 g of hydroxyethyl cellulose and 10 g of the mixed dry powder prepared in step S4 are weighed and put into a beaker, and then 230 mL of the mixed extract prepared in step S1 and 95 mL of deionized water are added, and the mixture is put into a water bath under stirring, and the temperature is always maintained at 58° C. and stirred for 4 hours. After the powder is completely dissolved and a suspension is formed, 32 mL of glycerol and 1.5 mL of glutaraldehyde are added, and the mixture is continuously stirred in a magnetic stirrer for 6 hours. The dispersed materials are added into a vacuum paste making machine, and the vacuum pump of the paste making machine is turned on to start vacuuming. After vacuum stirring for 35 minutes, the vacuum pump and the vacuum paste making machine are turned off for stirring, and the toothpaste is filled into a hose, and the tail is sealed with a tail sealing machine to obtain an anti-allergic, anti-caries and whitening toothpaste.

10. The anti-sensitivity and anti-caries toothpaste prepared according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Anti-allergic and anti-inflammatory toothpaste and preparation process thereof

    CN118476972A